PENGARUH SUHU DAN WAKTU KARBONISASI TERHADAP NILAI KALOR DAN KARAKTERISTIK PADA PEMBUATAN BIOARANG BERBAHAN BAKU PELEPAH AREN (Arenga pinnata) (Jurnal Teknik Kimia USU, 2015)
The availability of the petroleum fuels that deprived from fossil is depleted with the increase of human population. The challenge for this fuel shortage crisis can certainly be anticipated with the manufacture of fuels deprived from renewable biomass. The study of this research is to create a biocharcoal deprived from sugar palm (Arenga pinnata) with the optimum carbonization time and temperature in order to obtain a biocharcoal with the highest calorific value. Biocharcoal is a charcoal created from biomass. The study of the determination of the optimum conditions for the manufacture of biocharcoal from sugar palm (Arenga pinnata) has a temperature variable of 300, 350, 400, 450 and 500 0C and time variable of 60, 90 and 120 minutes. Sugar palm was first cut into a small pieces and dried up under the sun and then put into a furnace to carbonate it according to the predetermined variables. The product from furnace was then put inside a desicator to cool it off for 30 minutes and then analyze it with moisture content test, ash content test, volatile matter content test, carbon content test and calorific value test. The best result was obtained at the temperature of 350 0C and 120 minutes of carbonization with the calorific value of 8611,2581 cal/gr, moisture content of %, ash content of %, volatile matter content of % and carbon content of %. Based of the calorific value obtained, the result shows that sugar palm (Arenga pinnata) biocharcoal could be utilize as an renewable alternative source fuels